A model for evaluating the micro-explosion of a single droplet of water-in-oil emulsions and the effect of hydrophilic surfactants on the phenomenon. (23rd November 2022) - Liu, Cao; Chen, Hui; Xu, Jinshan; Xu, Jun; Cui, Lingrui; Cen, Lian; Cao, Fahai; Xiao, Tiancun
Graphical abstract: Highlights: A single droplet volume calculation model is developed. A new method for evaluating the micro-explosion of a single droplet is built up. The method was verified by a single droplet micro-explosion visualization experiment. Water-soluble surfactants enhance micro-explosion intensity of water-in-oil emulsion. Water-soluble surfactants enhance the superheat of water in water-in-oil emulsion. Abstract: The micro-explosion phenomenon of emulsified fuel when heated is known to improve thermal efficiency of combustion and reduce pollutant emissions. In this study, a new methodology is developed to evaluate the intensity and atomization effect of micro-explosion on a model droplet volume. The micro-explosion phenomenon of water-in-oil emulsified fuels prepared with different surfactants was studied using a single droplet micro-explosion shadow-imaging apparatus, and the proposed evaluation methods were verified. The results show that this new method can accurately predict the intensity and atomization effect of a single droplet undergoing micro-explosion. In addition, the addition of water-soluble surfactants effectively improves the intensity and atomization effect of the micro-explosion phenomenon in heterogeneous nucleation.